Understanding nursing research : building an evidence-based practice - Burns, Nancy; Gray, Jennifer , 1955-; Grove, Susan K. (Elsevier Saunders, 2011)
Focuses on evidence-based practice to demonstrate how the steps of the research process relate to evidence-based nursing. This text offers insights into understanding, appraising, and applying published research to evidence-based practice